Berlioz's Harold in Italy: leading softly. Issue 1 (March 2016) - Bathurst, Ralph
Abstract : This paper explores Harold in Italy, a symphony by Hector Berlioz. It offers a way of conceiving of organizational leadership beyond the controls of a hero figure and proposes alternative ways of being that facilitate group interactions. Subtlety of gesture, non-action, a willingness to respond to the promptings of others by being able to perceive what is occurring in the moment, are qualities that are discussed.